The male ScreenING Study: prevalence of HPV‐related genital and anal lesions in an urban cohort of HIV‐positive men in Germany. (1st February 2016) - Fuchs, W.; Wieland, U.; Skaletz‐Rorowski, A.; Brockmeyer, N.H.; Swoboda, J.; Kreuter, A.; Michalik, C.; Potthoff, A.; ,
Abstract: Background: Human papillomaviruses (HPV) induce condylomata, anogenital cancers and their precursor lesions as anal or penile intraepithelial neoplasia (AIN/PIN). HIV‐positive individuals have an increased risk for the development of anogenital HPV‐induced lesions. Objective: Estimation of the prevalence of HPV‐related anogenital benign and malignant lesions in HIV‐infected men attending a screening programme. Methods: Four hundred HIV‐positive men [98% men who have sex with men (MSM)] were enrolled in this prospective study from 2008 to 2011. All patients received an inspection of the anogenital region, digital rectal examination, high‐resolution anoscopy (HRA), anal cytology, anal/penile histology if required, and HPV‐typing of anal and penile swabs. Results: At baseline, 75% ( n = 302) of the men had abnormal anal cytological/histological results. 41% presented with low‐grade ( n = 164), 24% with high‐grade anal dysplasia ( n = 95) and two men with invasive anal cancer. 2.3% had PIN ( n = 9) and one patient had penile cancer at baseline. Throughout the study period, 75% had anal dysplasia (low‐grade n = 177, high‐grade n = 125), 3.3% ( n = 13) had PIN and two further patients developed anal cancer. Within the study period, 52.8% ( n = 211) had condylomata (49% anal, 15% penile, 11% anal plus penile condylomata). At baseline, 88.5% of anal and 39.3% of penile swabs were HPV‐DNA positive, and 77.8% of anal and 26.5% of penile swabs carried high‐risk HPV‐types. HPV16 was the most frequent HPV‐type. Conclusion: HIV‐positive MSM have a high risk for HPV‐induced condylomata, (pre)malignant anogenital lesions and anogenital cancers. Screening for HPV‐induced dysplasia is crucial to avoid progression to invasive carcinomas. Additionally, HPV‐vaccination recommendations should be extended to high‐risk populations.